Global Development Finance 2012 : External Debt of Developing Countries - World Bank (World Bank, 2012)
The data and analysis presented in this edition of global development finance are based on actual flows and debt related transactions for 2010 reported to the World Bank Debtor Reporting System (DRS) by 129 developing countries. The reports confirm that in 2010 international capital flows to developing countries surpassed preliminary estimates and returned to their pre-crisis level of $1.1 trillion, an increase of 68 percent over the comparable figure for 2009. Private capital flows surged in 2010 driven by a massive jump in short-term debt, a strong rebound in bonds and more moderate rise in equity flows. Debt related inflows jumped almost 200 percent compared to a 25 percent increase in net equity flows. The rebound in capital flows was concentrated in a small group of 10 middle income countries where net capital inflows rose by an average of nearly 80 percent in 2010, almost double the rate of increase (44 percent) recorded by other developing countries. These 10 countries accounted for 73 percent of developing countries gross national income (GNI), and received 73 percent of total net capital flows to developing countries in 2010. The 2010 increase in net capital flows was accompanied by marked change in composition between equity and debt related flows. Over the past decade net equity flows to developing countries have consistently surpassed the level of debt related flows, reaching as high as 97 percent of aggregate net capital flows in 2002 and accounting for 75 percent of them ($509 billion) in 2009. However, periods of rapid increase in capital flows have often been marked by a reversal from equity to debt.